Computing the Szeged and PI Indices of HAC5C7[p,q] and HAC5C6C7[p,q] Nanotubes by GAP Program - TAHERKHANI, B.; IRANMANESH, ALI; ALIZADEH, YASER (Asian Journal of Chemistry, 2010)
In this paper we give a GAP program for computing the Szeged and the PI indices of any graph. We also compute the Szeged and PI indices of HAC5C7[p,q] and HAC5C6C7[p,q] nanotubes by this program.